Evaluation of oxidative DNA damage in elderly patients with type 2 Diabetes mellitus living in Ivoti, State of Rio Grande do Sul - Larissa Carlos da Silva; Daiane Bolzan Berlese; Gustavo Muller Lara; Geraldine Alves dos Santos; Gilson Luis da Cunha (Universidade Estadual de Maringá, 2018)
Due to the increase in life expectancy and changes in eating habits, the elderly and obese population has increased in recent years. The objective of this study was to analyze the correlation between type 2 Diabetes mellitus (DM2) and oxidative DNA damage in elderly residents of the municipality of Ivoti, State of Rio Grande do Sul. This study had an exploratory, descriptive, cross-sectional and quantitative approach based on the data bank of the institutional project of the Feevale University. There was a predominant population of married women, retired, with monthly income up to 2 minimum wages, with education until to the 4th grade of fundamental school and bilingual. Statistical difference was detected for fasting glycemia, HbA1c and 8-hydroxydioxy-2-guanosine (8-OHdG) between DM2 and control subjects, as well as a positive Spearmann correlation between HbA1c and 8-OHdG in patients with DM2. It was possible to identify through fasting glycemia and HbA1c that elderly people who had poor glycemic control also showed a significant increase in the production of reactive oxygen species and consequent DNA damage when compared to the elderly with good glycemic control.